FEATURES OF QUALITY ASSESSMENT AND STANDARDIZATION PROSPECTS OF FATTY OILS AND OIL EXTRACTS FOR PHARMACEUTICAL PURPOSES (REVIEW) - E. V. Semina; P. S. Klimovich; A. O. Dolinkin; E. V. Parfenova; K. A. Rubina (Разработка и регистрация лекарственных средств)
Today technologies stimulating growth and stabilization of new blood vessel, regulating trajectory of vascular growth are promising for the treatment of ischemia. These technologies represent a therapeutic angiogenesis. Its are essential in the rapidly developing regenerative medicine. In the present work we describe the development and validation methods for determining the specific impurities (purity) gene therapeutic drug using the electrophoresis method in agarose gel followed by densitometry of electrophoretogram. This drug is designed for the treatment of lower limb ischemia. This drug is a combination preparation containing a mixture of DNA plasmid encoding the gene of hepatocyte growth factor and gene of Angiopoietin-1.